Executive function and dangerous driving behaviors in young drivers - Hayashi, Yusuke (Transp Res Part F Traffic Psychol Behav, 2018)
The purpose of the present study was to investigate the behavioral and cognitive processes underlying dangerous driving behaviors. We used a survey to assess levels of executive function in college students. The sample consisted of 59 males and 77 females and their age ranged from 18 to 24. We stratified the students into two groups based on executive function scores and compared the extent to which each group engaged in four dangerous driving behaviors (texting while driving, driving without a seat belt, driving while intoxicated, and speeding) as well as how often they experienced three negative driving outcomes (crashes, pulled over, and ticketed). We also investigated how these driving behaviors and outcomes are correlated with subcategories of executive function. The results show that students with a low level of executive function were more likely to engage in dangerous driving behaviors and more likely to experience negative driving outcomes. The results also show that texting while driving, driving while intoxicated, and speeding were most strongly correlated with the executive function subcategory of Impulse Control, whereas driving without a seat belt was most strongly correlated with the executive function subcategory of Strategic Planning. These results suggest that different behavioral or cognitive processes are involved in different dangerous driving behaviors and different interventions may be needed to target each underlying process.